2022
DOI: 10.29354/diag/156384
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal efficiency of nanofluid flows in a flat solar collector using CFD

Abstract: Flat plate solar collector (FPSC) is popular for their low cost, simplicity, and ease of installation and operation. In this work, FPSC thermal performance was analyzed. It's compared to diamond/H2O nanofluids. The volume percentage and kind of nanoparticles are analyzed numerically that validation with experimental data available in the literature. The hot climate of Iraq is employed to approximate the model. The numerical study is performed by using ANSYS/FLUENT software to simulate the case study of problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The study explored pressured convection with Al2O3/water nanofluid interior a horizontal duct with a BFS. The Nusselt range rose with better Reynolds numbers and increasing nanoparticle volume fractions as indicated from the previous observe [15]. Investigating float and warmth switch properties, a computational model analysed blended convective laminar fluid float over a 3dimensional MBFS with a Reynolds variety of 35.…”
Section: Introductionmentioning
confidence: 59%
“…The study explored pressured convection with Al2O3/water nanofluid interior a horizontal duct with a BFS. The Nusselt range rose with better Reynolds numbers and increasing nanoparticle volume fractions as indicated from the previous observe [15]. Investigating float and warmth switch properties, a computational model analysed blended convective laminar fluid float over a 3dimensional MBFS with a Reynolds variety of 35.…”
Section: Introductionmentioning
confidence: 59%
“…By maintaining a 2cm gap between the glass and the absorbing plate, the researcher found that doubling the glass plates' arrangement doubled the efficacy of the flat-solar collector as compared to a single glass plate. Zarda et al [12] studied the thermal performance of flat-plate solar collectors (FPSCs), which are known for their cost-effectiveness, simplicity, and ease of use. They focused on improving the efficiency of these collectors by introducing diamond/H 2 O nanofluids, a type of fluid containing tiny diamond particles.…”
Section: Introductionmentioning
confidence: 99%